The perceptions of Lithuanian hunters towards African swine fever using a participatory approach - Evelina Stončiūtė; Alvydas Malakauskas; Franz J. Conraths; Marius Masiulis; Carola Sauter-Louis; Katja Schulz (BMC Veterinary Research, 2022)
Abstract Background African swine fever (ASF) has been present in Lithuania since 2014. The disease affects mainly the wild boar population. Thus, hunters play a key role in the performance of disease surveillance and control measures. We used participatory methods to gain insight into the knowledge of hunters and to include their perceptions in the design and the implementation of surveillance and control measures to increase their effectiveness. Results The willingness and the interest of hunters to participate was high, but only eight focus group meetings with 33 hunters could be held due to the COVID-19 pandemic. The overall knowledge of Lithuanian hunters regarding ASF, investigated by semi-structured interviews, was sufficient to understand their part in ASF control and surveillance. However, their knowledge did not necessarily lead to an increased acceptance of some ASF control measures, like the targeted hunting of female wild boar. Participating hunters showed a good understanding of the processes of the surveillance system. Their trust in the performance within this system was highest towards the hunters themselves, thus emphasizing the importance of acknowledging their role in the system. Hunters refused measures including the reduction of hunting activities. They feared a complete elimination of the wild boar population, which in turn demonstrates the necessity to increase professional information exchange. Conclusions The perceptions of Lithuanian hunters regarding ASF surveillance and control in wild boar resembled those obtained in neighboring countries. It is imperative to communicate the results with decision-makers, to consider the views of hunters, when designing or adapting measures to control ASF in wild boar and to communicate with hunters on these measures and their justification.